Examining the Obesogenic Attributes of the Family Child Care Home Environment: A Literature Review - Lucine Francis; Lara Shodeinde; Maureen M. Black; Jerilyn Allen (Hindawi Limited, 2018)
Childhood obesity is a major public health concern in the US. More than a third of young children 2-5 years old are placed in nonrelative child care for the majority of the day, making the child care setting an important venue to spearhead obesity prevention. Much of the obesity research in child care has focused on center-based facilities, with emerging research on Family Child Care Homes (FCCHs)-child care operated in a home setting outside the child's home. The purpose of this review was to assess the obesogenic attributes of the FCCH environment. A search of the PubMed, Embase, CINHAL, and PsycINFO electronic databases identified 3,281 citations; 35 eligible for full-text review, and 18 articles from 17 studies in the analysis. This review found a lack of comprehensive written nutrition and physical activity policies within FCCHs, lack of FCCH providers trained in nutrition and physical activity best practices, lack of adequate equipment and space for indoor and outdoor playtime activities in FCCHs, inaccurate nutrition-related beliefs and perceptions among FCCH providers, poor nutrition-related communication with families, and poor feeding practices. Future research focusing on interventions aimed at addressing these problem areas can contribute to obesity prevention.